1982
DOI: 10.1901/jaba.1982.15-295
|View full text |Cite
|
Sign up to set email alerts
|

Programming “Loose Training” as a Strategy to Facilitate Language Generalization

Abstract: This study investigated the generalization of spontaneous complex language behavior across a nontraining setting and the durability of generalization as a result of programming and "loose training" strategy. A within-subject, across-behaviors multiple-baseline design was used to examine the performance of two moderately retarded students in the use of is/are across three syntactic structures (i.e., "wh" questions, "yes/no" reversal questions, and statements). The language training procedure used in this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

1983
1983
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 6 publications
0
16
0
1
Order By: Relevance
“…Substantial generalization resulted from use of (a) a "mand-model" technique with language-deficient preschool children (Rogers-Warren & Warren, 1980), (b) a "delay procedure" with severely language-delayed retarded children (Halle, Baer, & Spradlin, 1981), (c) "loose training" with moderately retarded children (Campbell & Stremel-Campbell, 1982), (d) "natural language training" with nonverbal autistic children (Koegel & O'Dell, 1982), and (e) "embedded instruction" with developmentally delayed, severely language-disordered children (Neef, Walters, & Egel, 1984). Although various components of these procedures differed from standard incidental teaching formats, each application involved prompting language in the context of naturally occurring stimuli.…”
Section: Princeton Child Development Institute Princeton New Jerseymentioning
confidence: 99%
“…Substantial generalization resulted from use of (a) a "mand-model" technique with language-deficient preschool children (Rogers-Warren & Warren, 1980), (b) a "delay procedure" with severely language-delayed retarded children (Halle, Baer, & Spradlin, 1981), (c) "loose training" with moderately retarded children (Campbell & Stremel-Campbell, 1982), (d) "natural language training" with nonverbal autistic children (Koegel & O'Dell, 1982), and (e) "embedded instruction" with developmentally delayed, severely language-disordered children (Neef, Walters, & Egel, 1984). Although various components of these procedures differed from standard incidental teaching formats, each application involved prompting language in the context of naturally occurring stimuli.…”
Section: Princeton Child Development Institute Princeton New Jerseymentioning
confidence: 99%
“…The strategy, which consisted of scripted play with gradually decreasing models and cued opportunities, was implemented for 19 to 28 sessions before 90% criterion was reached for the four children. Other research has also indicated that achievement of generalized and automatized production of forms lags well behind high and stable performances in supportive teaching contexts (Campbell and Stremel-Campbell, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…However, theory and experimental re search support the efficacy of individual model com ponents. Successful skill acquisition by learners with moderate to severe disabilities has been shown in studies that have distributed training trials within an instructional session (e.g., Dunlap, 1984;Kayser, Billingsley, & Neel, 1986;Mulligan, Lacy, & Guess, 1982) and across several different classroom activities or school routines (e.g., Campbell & Stremel-Campbell, 1982;Hunt, Goetz, Alwell, & Sailor, 1986). Further more, trial distribution alone (i.e., without functional trial sequencing and in-context instruction), has been shown to have advantages over the traditional massed trial training format.…”
mentioning
confidence: 99%